The Development of a Postgraduate Orthopaedic Manual Therapy Residency Program in Nairobi, Kenya - Cunningham, Shala; Jackson, Richard; Muli, Daniel Kangutu; McFelea, Joni (Frontiers in Public Health, 2017)
Introduction: There are very few opportunities for long term, comprehensive post-graduate education in developing countries because of fiscal and human resource constraints. Therefore, physiotherapists have little opportunity following graduation to advance their skills through the improvement of clinical reasoning and treatment planning and application. Background: To address the need for sustainable advanced instruction in physiotherapy within the country, a post-graduate Residency program was initiated in Nairobi, Kenya in 2012. The mission of the program is to graduate advanced orthopaedic practitioners who can lead their communities and local profession in the advancement of clinical care and education. Since its inception, six cohorts have been initiated for a total of 90 resident participants. In addition, six program graduates are being trained to continue the Residency program and are serving as teaching assistants for the on campus modules. This training will result in a self-sustaining program by 2020. Discussion: The manual therapy Residency education model allowed for advancement of the participating physiotherapists professional development utilizing evidence based practice. This was done without altering the current education system within the country, or accessing expensive equipment. Concluding Remarks: The Residency program was developed and established with the cooperation of a local education institution and a non-profit corporation in the United States. This collaboration has facilitated the advancement of orthopaedic clinical standards in the country and will, hopefully, one day serve an as a template for future programs.